Environmental Impacts of Photovoltaics: The Effects of Technological Improvements and Transfer of Manufacturing from Europe to China. Issue 6 (30th May 2018) - Stamford, Laurence; Azapagic, Adisa
Abstract: Solar power deployment is expanding rapidly alongside improvements in manufacturing processes and solar technology performance. This expansion has coincided with great cost reductions and a shift in manufacturing to China, but the environmental effects of these developments remain unclear. This study uses life cycle assessment (LCA) to estimate the environmental impacts for silicon‐based photovoltaic (PV) systems installed in two locations—the United Kingdom (UK) and Spain—in the years 2005 and 2015 to assess the changes that have occurred in the past decade. Manufacturing is considered in both Europe and China to analyze the effects of the aforementioned market shift. The results show that technological improvements have reduced the environmental impacts by an average of 45 %, ranging from 29 % (eutrophication) to 80 % (ozone layer depletion); the carbon footprint has been approximately cut in half. However, the shift of manufacturing to China has increased environmental impacts by an average of 9–13 % relative to manufacturing in Europe. Acidification is much higher for Chinese‐made systems, negating all of the technological progress that has been made over the past decade. Thus, the future impacts of PV are highly dependent upon environmental improvements in the Chinese energy mix. Learning rates for environmental impacts are estimated at 6–26 %, thereby leading to expected impact reductions of 8–34 % by the year 2025, which would bring the impacts of Chinese‐made PV systems back down to the levels currently achieved by systems made in Europe. Abstract : Sunny side up : The costs of solar photovoltaics (PV) have fallen dramatically in the last decade but changes to its environmental credentials are unclear. This study considers the environmental implications of technological improvements and a shift in PV manufacture from Europe to China. Technological progress has reduced impacts by 29–80 %, but the shift to China has eroded these gains by an average of ≈10 %. Learning rates predict environmental improvements of 8–34 % by 2025.